“…Wordwall is quite easy”: Students’ perceptions of using online platforms as English learning media - Putri Kurniawan Aprilia; Dwi Fita Heriyawati; M. Galuh Elga Romadhon; Zalsa Febrina Syabilla (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
This study examined secondary school students' perceptions of the use of utilizing Wordwall.net and filled a research gap on the innovative learning tool for secondary school students. The researcher employed a qualitative approach. Data were collected from five private junior high school students in Malang. Data from a semi-structured interview were acquired, and a descriptive-analytic technique was used to analyze the data. The data analysis revealed that the enthusiasm for learning English using the Wordwall.net application was evident among the students. This software offered a variety of original and engaging English language learning games. In Wordwall.net games, students get the chance to learn about English materials. This investigation showed that Wordwall.net had both benefits and obstacles of use for students using it as an English learning media. Additionally, Wordwall.net was successfully utilized as an innovative English learning tool to give students more engaging questions. As a result of this study, it was advised that English teachers, particularly those in secondary schools, use the Wordwall.net program since it can encourage students to take an active role in learning English.